Prime Quadratics

Algebra Level 2

Let a x 2 + b x 2 c + 1 = 0 ax^2+bx-2c+1=0 is a quadratic equation where a, b & c are prime numbers such that 1 is a root of this equation. If 2 b + 3 c = 25 2b+3c=25 is true for the above equation. Then find the values for a, b & c.

a=6, b=3, c=8 a=13, b=3, c=5 a=2, b=2, c=11 a=11, b=2, c=7

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Anandmay Patel
Oct 5, 2016

As 1 is a root of the equation,therefore, \text{As 1 is a root of the equation,therefore,} a + b 2 c + 1 = 0 a+b-2c+1=0 . which is equivalent to \text{which is equivalent to} a + b + 1 2 = c \dfrac{a+b+1}2=c .

As c is a natural prime number,it is clear that a+b must be odd.But a and b are also primes. \text{As c is a natural prime number,it is clear that a+b must be odd.But a and b are also primes.} All primes except 2 are odd. \textit{All primes except 2 are odd.}

And the sum of 2 numbers can be odd if and only if they both have different parity.So one is odd,other is even. \text{And the sum of 2 numbers can be odd if and only if they both have different parity.So one is odd,other is even.}

This implies that if a is an odd prime,then b is necessarily 2,and if b is an odd prime,then a is necessarily 2. \text{This implies that if a is an odd prime,then b is necessarily 2,and if b is an odd prime,then a is necessarily 2.}

So,either a or b is 2,but not both.This eliminates the first 3 options.So the answer must be option d.) \text{So,either a or b is 2,but not both.This eliminates the first 3 options.So the answer must be option d.)} .

Tapas Mazumdar
Oct 5, 2016

Let,

a x 2 + b x 2 c + 1 = ( x 1 ) ( a x + k ) a x^2 + bx - 2c + 1 = \left( x-1 \right) \left(ax + k \right)

Expanding the RHS of this equation, we get,

a x 2 + b x 2 c + 1 = a x 2 + k x a x k = a x 2 + ( k a ) x k \begin{aligned} a x^2 + bx - 2c + 1 &= a x^2 + kx - ax - k \\ & = a x^2 + \left(k-a \right) x - k \end{aligned}

Comparing terms on both sides, we obtain,

k = 2 c 1 ( 1 ) k = a + b ( 2 ) k = 2c - 1 \ \cdots(1) \\ k = a + b \ \cdots(2)

Consider the equation 2 b + 3 c = 25 2b + 3c = 25 , here,

c = 25 2 b 3 c = \dfrac{25- 2b}{3}

Substituting the value of c c in ( 1 ) (1) gives,

k = 47 4 b 3 k = \dfrac{47 - 4b}{3}

Equating this value of k k with ( 2 ) (2) gives,

47 4 b 3 = a + b 3 a + 7 b = 47 \begin{aligned} \dfrac{47 - 4b}{3} &=& a+b \\ \implies 3a + 7b &=& 47 \end{aligned}

Which gives,

a = 11 b = 2 a = \boxed{11} \\ b = \boxed{2}

as the only prime solution.

Therefore,

c = 7 c = \boxed{7}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...